PELATIHAN DAN PENDAMPINGAN PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN TEMATIK BAGI SISWA KELAS V SD NEGERI 67 KOTA BENGKULU - Agusdianita, Neza; Karjiyati, Karjiyati; Nuliantini, Nani (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this study is to increase teachers ' knowledge of the implementation of Project-Based Learning models (PjBL) in thematic learning, to improve teacher skills in designing implementing and evaluating learning That is meaningful, active, innovative, creative, and fun. The method used in this PPM activity is training and mentoring. The instruments used in this PPM activity are observation sheets, interview sheets, and training modules. Data analysis of this activity is descriptively qualitative. The results of this study were carried out training activities and mentoring the implementation of Project-Based Learning Model (PjBL) in thematic learning.Â